The beneficial pharmacological effects of Uncaria rhynchophylla in neurodegenerative diseases: focus on alkaloids - Chen, Leilei; Liu, Yingjuan; Xie, Junxia (Frontiers in Pharmacology, 2024)
With the intensification of aging population, the prevention or treatment of neurodegenerative diseases, such as Parkinson’s disease and Alzheimer’s disease, has drawn more and more attention. As a long used traditional Chinese medicine, Uncaria rhynchophylla (Miq.) Jacks., named Gouteng in Chinese, has been reported to have an effective neuroprotective role in neurodegenerative diseases. In this review, the beneficial pharmacological effects and signaling pathways of herbal formulas containing U. rhynchophylla, especially major compounds identified from U. rhynchophylla, such as corynoxine B, corynoxine, rhynchophylline, and isorhynchophylline, in neurodegenerative diseases, were summarized, which not only provide an overview of U. rhynchophylla for the prevention or treatment of neurodegenerative diseases but also give some perspective to the development of new drugs from traditional Chinese medicine.